Search for patterns by combining cosmic-ray energy and arrival directions at the Pierre Auger Observatory - Aab, A.; Abreu, P.; Aglietta, M.; Ahn, E. J.; Al Samarai, I.; Albuquerque, I. F. M.; Allekotte, Ingomar; Allen, J.; Allison, P.; Almela, Daniel Alejandro; Alvarez Castillo, J.; Alvarez Muñiz, J.; et al. (Springer, 2015)
Fil: Aab, A.. Universitat Siegen; Alemania